Neurofilament Light Chain Assessment in Type 2 Diabetic Patients with Distal Symmetrical Polyneuropathy - Israa Abdelmalik Salem; Sura Ahmed Abdulsattar; Haider Fadhil Alrubaye (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Background: A neuron-specific cytoskeletal protein called Neurofilament light chain is present in the cytoplasm of myelinated axons especially those with a large diameter which is essential for maintaining the size as well as for structural support.